Comparative Analysis of the Application of AHP and SAW in the Selection of the Best Employees at the Main Samsat Office, Samarinda City. - Darmawan, Dwiki Adi; Arbansyah, Arbansyah; Latipah, Asslia Johar (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2024)
Employees are a supporting factor in a company or agency, because with employeeswho have company qualification standards, the company's productivity will be maintained and will increase. The AHP and SAW methods can be used to determine the best employees. There are 3 criteria and 16 alternatives that are given a value based on the scale of importance and weight for each criterion that has been determined by the Samarinda City Samsat Main Office which will be processed to find a sensitivity value using two methods, namely AHP and SAW. By carrying out the calculation process as much as 6 times the weight addition experiment where each weight is added to the value of 0.5 and 1 which is applied to the two AHP and SAW methods produces the sensitivity values of the two methods and uses two experiments with the first formula (XA – XB) and ( XA + XB ) then the sensitivity value obtained from the first trial of the AHP method is - 2.592705356 and the sensitivity value of the SAW method is -4.522690058. The second experiment added the value (XA + XB) so that the results of the sensitivity values of the two methods were obtained, namely AHP 5.952672848 and SAW method 8.358567251. From the calculations of these two methods, the SAW method was chosen which is more sensitive, so the best employee with the highes score at the Samsat Main Office, Samarinda City, was A1, namely the Selvi Salamah alternative, with a priority value of0.944444444.